2020
DOI: 10.1021/acsomega.0c00524
|View full text |Cite
|
Sign up to set email alerts
|

Copper(I)-Mediated 11C-Carboxylation of (Hetero)arylstannanes

Abstract: A novel copper-mediated carboxylation strategy of aryl- and heteroaryl-stannanes is described. The method serves as a mild (i.e., 1 atm) carboxylation method using stable carbon dioxide and is transferable as a radiosynthetic approach for carbon-11-labeled aromatic and heteroaromatic carboxylic acids using sub-stoichiometric quantities of [11C]­CO2. The methodology was applied to the radiosynthesis of the retinoid X receptor agonist, [11C]­bexarotene, with a decay-corrected radiochemical yield of 32 ± 5% and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 53 publications
0
14
1
Order By: Relevance
“…[38] At the same time, the preparation of 11 C-labeled carboxylic acids from aryl stannane precursors and [ 11 C]CO 2 via a copper-mediated carboxylation was reported by other authors. [41][42][43] We decided to explore if this reaction could be applied to stannane Tz derivatives as well. Aryl stannane Tzs 1 and 2 and the corresponding carboxylic acid derivatives 3 and 4 were synthesized as previously reported from the corresponding nitriles with overall yields of 20%-40% (Section S3, Supporting Information) (Scheme 2).…”
Section: Synthesis Of Tetrazine Derivatives For 11 C-labelingmentioning
confidence: 99%
See 1 more Smart Citation
“…[38] At the same time, the preparation of 11 C-labeled carboxylic acids from aryl stannane precursors and [ 11 C]CO 2 via a copper-mediated carboxylation was reported by other authors. [41][42][43] We decided to explore if this reaction could be applied to stannane Tz derivatives as well. Aryl stannane Tzs 1 and 2 and the corresponding carboxylic acid derivatives 3 and 4 were synthesized as previously reported from the corresponding nitriles with overall yields of 20%-40% (Section S3, Supporting Information) (Scheme 2).…”
Section: Synthesis Of Tetrazine Derivatives For 11 C-labelingmentioning
confidence: 99%
“…Compounds 1 and 2 were reacted with [ 11 C]CO 2 using the same conditions for arylstannane 11 C-carboxylation reported by Duffy et al [41] Both compounds were successfully radiolabeled to give respectively [ 11 C]3 and [ 11 C]4. However, in order to use these compounds for the radiolabeling of TCO-modified polymers, we had to solve two issues.…”
Section: Optimization Of Cu-mediated 11 C-carboxylation Of Tetrazinesmentioning
confidence: 99%
“…Currently, the following methods are utilized for the synthesis of various 11 C-radiotracers through C–C bond formation. The alkylation of carbanions (nucleophiles) with carbon-11-labeled alkyl halides, nitroalkanes, and cyanide (electrophilic carbon-11) The carboxylation of organometallic reagents, copper, and other metal-mediated catalysts. , Transition-metal-mediated (palladium, rhodium, and selenium) chemical reactions with [ 11 C]­CH 3 I and [ 11 C]­CO. Various carbon-11 radiotracers are synthesized through C–C bond formation using different well-known reaction mechanisms like Stille reaction (Pd 2 (dba) 3 / 11 CH 3 I) for [ 11 C]­A85380 (nicotinic Ach receptor agonist) ( 19 ), Negishi coupling reaction (Pd­(PPh 3 ) 2 Cl 2 / 11 CH 3 I) for [ 11 C]­MPEP (glutamate receptor subtype 5 receptors) ( 20 ), Suzuki cross-coupling reaction (Pd­(PPh 3 ) 2 Cl 2 / 11 CO) for N -[ 11 C]­phenylacetamide derivative (HIV-1 reverse transcriptase inhibitor) ( 21 ), Heck reaction (Pd 2 (dba) 3 / 11 CH 3 I) for [ 11 C]­stilbene derivative (targeting amyloid plaques) ( 22 ), Sonogashira reaction (Pd 2 (dba) 3 / 11 CH 3 I) for N -[ 11 C]­estradiol derivative (estrogen receptors agonist) ( 23 ), and 11 C-cyanide cross-coupling reaction (Pd 2 (dba) 3 / 11 CN) for [ 11 C]­cyanide derivative (dopamine D3 receptor antagonist) ( 24 ) (Figure ). …”
Section: Introductionmentioning
confidence: 99%
“…54,55 • Transition-metal-mediated (palladium, rhodium, and selenium) chemical reactions with [ 11 C]CH 3 I and [ 11 C]CO.56−59 …”
mentioning
confidence: 99%
“…Direct carboxylation of (hetero)­aromatic compounds is particularly attractive because the ubiquitous structural motifs of the corresponding carboxylic acids are commonly found in pharmaceuticals, organic materials, and commodity chemicals . Due to the high thermodynamic stability of CO 2 , most of the C–H carboxylation reactions proceed via a reactive carbanion intermediate, which is formed owing to the use of high-energy chemicals such as Grignard reagents or alkyl lithium reagents (Scheme A). However, these reactions generally require low temperature and have low functional-group tolerance. Previous studies have shown that Au­(I) and Cu­(I) species can activate the sp 2 C–H bonds of electron-deficient (hetero)­arenes .…”
Section: Introductionmentioning
confidence: 99%